COMMUNICATION STRATEGY OF THE NEI-DT FOUNDATION IN BUILDING COMMUNITY TRUST THROUGH A COMMUNITY-BASED HEALTHCARE SERVICE PROGRAM - Saviera Zahra Aziza; Dwi Kartikawati (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the communication strategy employed by the NEI-DT Foundation in building community trust through a community-based healthcare service program in Tritunggal Hamlet, Banyuasin Regency, South Sumatra, Indonesia. The study is motivated by the importance of organizational communication strategies in enhancing public participation and program legitimacy within rural communities characterized by limited access to information, geographical constraints, and community-oriented social structures. Adopting a constructivist paradigm, this research employs a qualitative approach using an intrinsic case study design. Data were collected through in-depth interviews, non-participant observation, and document analysis involving seven informants, including foundation representatives, community leaders, and program beneficiaries. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings reveal that the foundation’s communication strategy involves identifying community characteristics, developing simple and contextually relevant messages, utilizing a combination of digital and traditional communication channels, and engaging local leaders as communication intermediaries. Program information is disseminated through village heads, neighborhood leaders, women’s community groups (PKK), social media platforms such as WhatsApp and Facebook, and mosque loudspeaker announcements. The study further demonstrates that the communication pattern reflects the Two-Step Flow of Communication model, in which community leaders function as opinion leaders who mediate organizational messages before they reach the wider community. Community trust is cultivated through the social legitimacy of local leaders, interpersonal communication, direct experiences with program benefits, and the consistency of services provided by the foundation. The study concludes that the effectiveness of community-based organizational communication strategies in rural settings is determined not only by message content and media utilization but also by the organization’s ability to establish interpersonal relationships, adapt communication practices to local cultural contexts, and actively involve community leaders within the communication network. This research contributes to the advancement of community-based organizational communication studies by providing empirical insights into trust-building processes in rural community development programs